EFEKTIVITAS PROGRAM PELAYANAN APLIKASI SIPADU (Sistem Informasi Pelayanan Administrasi Desa Terpadu) DALAM PENGOPTIMALAN PELAYANAN ADMINISTRASI DI DESA DANGIN PURI KANGIN KECAMATAN DENPASAR UTARA - Widanti, Ni Putu Tirka; Pinatih, Dewa Ayu Agung Intan (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2024)
This research aims to find out how effective the SIPADU Application Service Program (Integrated Village Administrative Service Information System) is in optimizing administrative services in Dangin Puri Kangin Village, North Denpasar District. The research method used is a qualitative descriptive research method using interview techniques were determined by random sampling and literature study were carried out by searching for information through journals, articles and internet sites. The research results show that the SIPADU (Integrated Village Administrative Services Information System) application in optimizing administrative services in Dangin Puri Kangin Village, North Denpasar District is quite effective. This refers to the effectiveness measurement proposed by Steers which consists. 1) Indicators for achieving goals are running well because they are designed according to community needs, but the level of socialization needs to be increased. 2) The adaptation indicators have been met because this application makes it easy for the public to obtain administrative and information services. 3) Integration indicators are also carried out well by the Dangin Puri Kangin Village Government through the delivery of information via its website and social media. Integration is also carried out through regular updates of information on the application. From this study it can be concluded that the SIPADU Application Service Program (Integrated Village Administrative Services Information System) in Optimizing Administrative Services in Dangin Puri Kangin Village, North Denpasar District is running quite effectively but there needs to be continuous increase in socialization to the community of Dangin Puri Kangin Village, North Denpasar District. Keywords: Effectiveness; SIPADU; Public Service